2021
DOI: 10.31289/jimbi.v2i1.452
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan dan keterlibatan kerja dalam meningkatkan kinerja Aparatur Sipil Negara (ASN) Fakultas Matematika Ilmu Pengetahuan Alam Universitas Sumatera Utara

Abstract: Preliminary; The USU Faculty of Mathematics and Science is an educational institution, to create an effective and efficient workplace, efforts are needed to achieve these goals. From the observations made, the phenomenon of problems that occur in job involvement and job training causes decreased performance. Destination; to determine the effect of training and overwork on the performance of ASN at the USU Faculty of Mathematics and Natural Sciences. Method; conducted associatively using a sample of 68 responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…This is in line with research conducted by (Julianry et al, 2017), (Putri & Prokosawati, 2022) which found that one of the efforts to improve human resource performance is to provide Human Resource development training through the Performance Management System program. The results of this study do not support research conducted by (Pane & Wijaya, 2021) which found that training had no significant effect on improving ASN performance at the Faculty of Mathematics and Natural Sciences, University of North Sumatra.…”
Section: Hypothesis Testcontrasting
confidence: 99%
“…This is in line with research conducted by (Julianry et al, 2017), (Putri & Prokosawati, 2022) which found that one of the efforts to improve human resource performance is to provide Human Resource development training through the Performance Management System program. The results of this study do not support research conducted by (Pane & Wijaya, 2021) which found that training had no significant effect on improving ASN performance at the Faculty of Mathematics and Natural Sciences, University of North Sumatra.…”
Section: Hypothesis Testcontrasting
confidence: 99%